2021
DOI: 10.1101/2021.09.23.21263948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demographic characteristics of SARS-CoV-2 B.1.617.2 (Delta) variant infections in Indian population

Abstract: Importance: Higher risks of contracting infection, developing severe illness and mortality are known facts in aged and male sex if exposed to the wild type SARS-CoV-2 strains (Wuhan and B.1 strains). Now, accumulating evidence suggests greater involvement of lower age and narrowing the age and sex based differences for the severity of symptoms in infections with emerging SARS-CoV-2 variants. Delta variant (B.1.617.2) is now a globally dominant SARS-CoV-2 strain, however, current evidence on demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…An incremental increase in transmissibility of the emerging variants from B.1 to B.1.617.2 suggests that more numbers of younger age individuals, including pediatric age group, may get involved in the pandemic as the strains further evolve 1,2,4,35,79. Also, early indications for narrowing the sex-based differences in patient outcomes is an important epidemiological concern.83,84 In a recent study, among the Indian population, using data fromthe national clinical registry for COVID-19 authors have compared clinical profiles of the hospitalized patients during two successive COVID-19 waves (N = 12 059 and 6903). The authors noted that the mean age of the patients was significantly lower in the second wave (48.7 [18.1] year vs. 50.7 [18.0] year, p < 0.001) with more numbers of patients in the younger age groups intervals (<20, and 20-39 year).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An incremental increase in transmissibility of the emerging variants from B.1 to B.1.617.2 suggests that more numbers of younger age individuals, including pediatric age group, may get involved in the pandemic as the strains further evolve 1,2,4,35,79. Also, early indications for narrowing the sex-based differences in patient outcomes is an important epidemiological concern.83,84 In a recent study, among the Indian population, using data fromthe national clinical registry for COVID-19 authors have compared clinical profiles of the hospitalized patients during two successive COVID-19 waves (N = 12 059 and 6903). The authors noted that the mean age of the patients was significantly lower in the second wave (48.7 [18.1] year vs. 50.7 [18.0] year, p < 0.001) with more numbers of patients in the younger age groups intervals (<20, and 20-39 year).…”
mentioning
confidence: 99%
“…The total mortality was about 1.8 times higher and the risk of death is increased irrespective of the sex (OR: 3.034, 95% CI: 1.7-5.2, p < 0.001). Interestingly, although, the proportion of mortality was still higher in men than women, an increased number of women (32% with Delta vs. 25% with B.1) died 84. F I G U R E 6 The global spread of emerging SARS-CoV-2 variants.…”
mentioning
confidence: 99%
“…In India, the proportion of women who became infected with the Delta variant increased (41% vs. 36%), as did the risk of mortality (odds ratio: 3.034, 95% CI: 1.7-5.2, p < 0.001), with a higher proportion of women dying compared to men (32% vs. 25%) [405].…”
Section: Gendermentioning
confidence: 98%
“…A study conducted by Hwang et al (2021) in South Korea showed that about half of affected people were under the age of 19 [404]. Kumar et al (2021) found that in comparison to the wild-type (B.1) strain, the Delta variant affected a higher proportion of younger age groups, particularly those younger than 20 years (0-9 years: 4.47% vs. 2.3%, 10-19 year: 9% vs. 7%) [405].…”
Section: Population Density Race and Life Conditionmentioning
confidence: 99%
“…When people arm themselves with vaccines, the SARS-CoV-2 virus mutates simultaneously. Alpha, Delta and Omicron variants rapidly took over their predecessors and became dominant, and they increased immune escape ability [14][15][16][17] and target cell affinity 40 , which, in turn, caused increased viral load 23 and symptomatic severity 41 , breaking through vaccine protection 42 and obtaining greater transmissibility 11 . We further incorporated the interactions between variants and the immune system into our computational framework and discussed how variants affect the individual-and population-level characters of primary infection and vaccine protection.…”
Section: Dynamics Of Sars-cov-2 Variants: Competition Between Viral V...mentioning
confidence: 99%